Potencial de biorremediação de Chlorella vulgaris (Chlorophyceae) em águas residuais do processamento da mandioca, Capítulo 9 - Medeiros, Verónica de (2022)
Most cassava processing industry generates a large volume of wastewater effluent with high contaminating load of COD and BOD and cyanide concentration, posing to a serious threat to the environment. A variety of processes has been tested to treat this wastewater effluent, where the effectiveness in reducing the toxicity varies greatly. Microalgae are photosynthetic microorganisms that can rapidly generate biomass from solar energy, CO2 and nutrients in water, namely those present in wastewater effluents. Also, algal biomass and algae-derived compounds are potentially useful in industrial applications, as well as for biodiesel production. Taking this into account, the aim of this work was evaluated the ability of Chlorella vulgaris to growth on cassava-processing effluent and assess the bioremediation potential by evaluating toxicity of effluent. Batch cultures, with C. vulgaris in suspended and in immobilized-cell systems, under different dilutions (20-50%) of cassava effluent were tested. The effectiveness of the process has been assessed by phytotoxicity, in germination trials of Lactuca sativa. Best results were obtained with C. vulgaris in immobilizedsystems and carried out with higher initial cell concentrations. Regarding the phytotoxicity, after biotreatment we can conclude that microalgae can reduce the toxicity of cassava effluent, leading to Germination Increase index (GI) range of 88-100%.